Environmental risk assessment of Tsunami-affected areas in Ishinomaki, Japan - Makita, K.; Inoshita, K.; Kayano, T.; Hagiwara, K.; Asakawa, M.; Ogawa, K.; Noda, J.; Sasaki, H.; Higuchi, H.; Iwano, H.; Tamura, Y. (International Livestock Research Institute, 2012)
PURPOSE On 11 March 2011, Tsunami caused by massive magnitude 9.0 earthquakes occurred at Sanriku offshore attacked Tohoku and North Kanto shores. As in February 2012, the total number of deaths and missing by this East Japan disaster was 19,139 and Ishinomaki was especially heavily affected; the number of death and missing 3,833 accounted for 20% of the total number. Rakuno Gakuen University sent 73 volunteers including 6 teaching and administrative staffs since April 2011 and its researchers started environmental risk assessment since July jointly with Ishinomaki City Council. METHODOLOGY Stratified random sampling of the Chonai-Kai administrative units with two strata, the extremely damaged areas by Tsunami located within two kilometers from the sea shore and 11kms along coast were divided into eastern and western strata from Old Kitakami River, was performed and 20 out of 87 units were selected. Sampling of sludge, water, flies, mosquitoes and rodents were conducted and the samples were served for microbiological, bio-chemical and chemical analyses. RESULTS AND DISCUSSION Before Tsunami, livestock feed factories were located on the western seashore from Old Kitakami River and fish processing factories and freezer storages on the eastern. These feeds and fish were scattered on the Tsunami affected areas and these areas smelled very bad. Plenty of Musca and Spaerocerdae species flies that favor carbonates occurred on the western seashore and plenty of Phomiaregina flies that favor proteins on the eastern in June and July. City Council, volunteers and Self Defense Force removed fish and feeds and conducted spraying pesticides and eventually the smell and flies were controlled by August. From the sludge and water samples, enterococcal bacteria and non-highly pathogenic Vibrio were isolated. Heavy metals were found but not in the alarming dose. Rodents seemed to die off other than one western area with canal. From these results, risk was not so high but continuous monitoring is recommended. Sociological studies needs to be carried out to understand people’s intention of living in the areas again in order to present the overall risks.